Earth Observation and Geospatial Analyses [Working Title] 2019
DOI: 10.5772/intechopen.86109
|View full text |Cite
|
Sign up to set email alerts
|

Application of Topographic Analyses for Mapping Spatial Patterns of Soil Properties

Abstract: Landscape topography is a key parameter impacting soil properties on the earth surface. Strong topographic controls on soil morphological, chemical, and physical properties have been reported. This chapter addressed applications of topographical information for mapping spatial patterns of soil properties in recent years. Objectives of this chapter are to provide an overview of (1) impacts of topographic heterogeneity on the spatial variability in soil properties and (2) commonly used topography-based models in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 161 publications
(215 reference statements)
1
11
0
Order By: Relevance
“…Our results are in agreement with earlier studies which reported relatively low values of SOC and STN at higher terrain elevations (Zhao et al, 2015). It is plausible that as terrain elevation decreases, soil moisture content and availability tend to increase (Hook and Burke, 2000), and consequently, increasing plant productions which in turn increases SOC input and accumulation (Pei et al, 2010;Li and McCarty, 2019). It is also possible that the accumulation of SOC at the lower position could be caused by soil erosion which leads to residue deposition and redistribution of labile organic carbon in the surface soil (Lal, 2003;Li et al, 2017).…”
Section: Topography Variables In Relation To Soil Quality Indicators In Different Land-usessupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with earlier studies which reported relatively low values of SOC and STN at higher terrain elevations (Zhao et al, 2015). It is plausible that as terrain elevation decreases, soil moisture content and availability tend to increase (Hook and Burke, 2000), and consequently, increasing plant productions which in turn increases SOC input and accumulation (Pei et al, 2010;Li and McCarty, 2019). It is also possible that the accumulation of SOC at the lower position could be caused by soil erosion which leads to residue deposition and redistribution of labile organic carbon in the surface soil (Lal, 2003;Li et al, 2017).…”
Section: Topography Variables In Relation To Soil Quality Indicators In Different Land-usessupporting
confidence: 93%
“…In addition to these land-use effects, topography is another soil-forming factor which dominantly affects soil properties at local scales (Jenny, 1941) through regulating soil hydrological regimes and controlling the gravity-driven soil movements (Speight, 1980;Li and McCarty, 2019). Accordingly, topography has been identified as one of the important sources of the heterogeneity of soil properties (Zhao et al, 2015;Burst et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sochava in his scientific work developed [6] the scientific basis for the stabilization and efficient use of the natural environment [27,31,9]. Geosystems are subdivided into planetary (geographical), regional (natural geographic zones, large countries, provinces and landscapes), and topological (structural, morphological parts of landscapes: place, urochishche, facies).…”
Section: Methodsmentioning
confidence: 99%
“…The method of relief plastics was used by [34] in his work. The top and bottom of the aquifers, which are the main elements of relief, are depicted as a line along the relief slope [31]. The relief plastic card clearly separates the boundaries of the on-site reservoirs.…”
Section: Methodsmentioning
confidence: 99%
“…The construction of the ABM requires the selection of the crop and geographic location, e.g., species, cultivar, soil properties. Based on aerial images of the field, image processing is performed, e.g., color to grayscale, binarization, edge detection and region extraction [31,32]. This processing yields a 2-D map, which can be discretized using a spatial grid.…”
Section: Agent Spatial Environmentmentioning
confidence: 99%